Can web-based community engagement inform equitable planning outcomes? A case study of bikesharing. Issue Volume 10:Issues 3(2017) (3rd July 2017) - Piatkowski, Daniel; Marshall, Wesley; Afzalan, Nader
Abstract: Web-based engagement is increasingly popular because of its perceived ability to increase access to the planning process with less effort than traditional methods. Currently, the utility of these approaches for meeting the needs of all members of a community is unclear. This research tests whether web-based engagement can forward equitable planning outcomes by examining proposed bikeshare station locations collected via a web-application; operationalizing equity as equal access to bikeshare station locations across all populations. Results indicate that solely relying upon online outreach would lead to an inequitable distribution of station locations. Suggested station locations are negatively-correlated with increased minority populations and positively-correlated with an increased mix of employment and housing. As such, we determine that while online outreach is a convenient and efficient means of collecting vast amounts of information, on its own it is not well-suited to planning applications in which access-equity is a primary concern.